PROBLEMATIKA PENCAPAIAN KOMPETENSI KETERAMPILAN BERBICARA SISWADALAM PEMBELAJARAN BAHASA INDONESIA - Siti Nur Afifatul Hikmah (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Learning language skills in schools does not only emphasize theory, but students are required to be able to use language as its function. Language skills in listening, writing, reading, and speaking are a component that cannot be separated from language activities. The ability to speak must also be able to analyze and ensure that what is said can be received appropriately by the listener. In fact, there are still various obstacles in speaking, both internal and external factors. Evaluation of learning to speak is still guided by speaking theory, not emphasizing speaking practice.